(untitled) - Sugiarto, Ahmad Singgih; Hidayati, Siti Nurul (PENSA E-JURNAL: PENDIDIKAN SAINS, 2019)
This research aimed to analyze the feasibility of the presentation of 4 science textbook for grade 8th junior high school, especially in the pressure chapter used in SMP Negeri 22 Surabaya. The type of research used in this study is qualitative research using descriptive analysis and data collection techniques using observation methods. The instruments used in this study refer to the feasibility instrument of a teaching book issued by the National Education Standards Agency (BSNP) which included the presentation of the material and the completeness of supporting the presentation of the material. The results of this study show that the teaching book requires several improvements. The improvements include the concept map presented, the addition of training questions, illustrations, glossaries and several references not yet listed in the bibliography. Keywords: Study of textbook, presentation feasibility, pressure